A novel porcine in vitro model of the blood-cerebrospinal fluid barrier with strong barrier function - Schroten, Mira Dorothea; Hanisch, Franz-Georg; Bechtoldt, Natascha; Stump-Guthier, Carolin; Riebe, Roland; Lenk, Matthias; Wolburg, Hartwig; Tenenbaum, Tobias; Schwerk, Christian (PLOS ONE, 2012)
Epithelial cells of the plexus choroideus form the structural basis of the blood-cerebrospinal fluid barrier (BCSFB). In vitro models of the BCSFB presenting characteristics of a functional barrier are of significant scientific interest as tools for examination of BCSFB function. Due to a lack of suitable cell lines as in vitro models, primary porcine plexus epithelial cells were subjected to a series of selective cultivation steps until a stable continuous subcultivatable epithelial cell line (PCP-R) was established. PCP-R cells grow in a regular polygonal pattern with a doubling time of 28-36 h. At a cell number of 1.5×105 in a 24-well plate confluence is reached in 56-72 h. Cells are cytokeratin positive and chromosomal analysis revealed 56 chromosomes at peak (84th subculture). Employing reverse transcription PCR mRNA expression of several transporters and components of cell junctions could be detected. The latter includes tight junction components like Claudin-1 and -3, ZO-1, and Occludin, and the adherens junction protein E-cadherin. Cellular localization studies of ZO-1, Occludin and Claudin-1 by immunofluorescence and morphological analysis by electron microscopy demonstrated formation of a dense tight junction structure. Importantly, when grown on cell culture inserts PCP-R developed typical characteristics of a functional BCSFB including high transepithelial electrical resistance above 600 Ω×cm2 as well as low permeability for macromolecules. In summary, our data suggest the PCP-R cell line as a suitable in vitro model of the porcine BCSFB.
Gesehen am 11.04.2018